BMP‐7 represses albumin‐induced chemokine synthesis in kidney tubular epithelial cells through destabilization of NF‐κB‐inducing kinase. Issue 5 (14th January 2014) - Lim, Ai Ing; Chan, Loretta Y Y; Tang, Sydney C W; Yiu, Wai Han; Li, Ruixi; Lai, Kar Neng; Leung, Joseph C K
Abstract : Protein overload activates proximal tubule epithelial cells (PTECs) to release chemokines. Bone morphogenetic protein‐7 (BMP‐7) reduces infiltrating cells and tissue damage in acute and chronic renal injuries. The present study examines the inhibitory effect and related molecular mechanism of BMP‐7 on chemokine and adhesion molecule synthesis by PTECs activated with human serum albumin (HSA). The expression profiles of chemokines and adhesion molecules in cultured human PTECs were screened by PCR array. Expression of CXCL1, CXCL2 and vascular cell adhesion protein 1 (VCAM‐1) by PTECs was significantly upregulated by HSA and reduced by BMP‐7. HSA activated both the canonical and noncanonical nuclear factor (NF)‐κB pathways in PTECs, as indicated by the increased nuclear translocation of NF‐κB p50 and p52 subunits. The nuclear translocation of NF‐κB p52 was completely abrogated by BMP‐7, whereas NF‐κB p50 activation was only partially repressed. BMP‐7 increased the expression of cellular inhibitor of apoptosis 1 (cIAP1), tumor necrosis factor receptor‐associated factor (TRAF)2 and TRAF3, but not of NF‐κB‐inducing kinase (NIK) that was significantly upregulated by HSA. Silencing NIK recapitulated the partial inhibitory effect on HSA‐induced chemokine synthesis by BMP‐7. Complete abolishment of the chemokine synthesis was only achieved by including additional blockade of the NF‐κB p65 translocation on top of NIK silencing. Our data suggest that BMP‐7 represses the NIK‐dependent chemokine synthesis in PTECs activated with HSA through blocking the noncanonical NF‐κB pathway and partially interfering with the canonical NF‐κB pathway.